Fouling evolution of extracellular polymeric substances in forward osmosis based microalgae dewatering. (1st February 2023) - Ji, Cheng-Cheng; Chen, Ke-Yu; Deng, Shao-Kang; Wang, Jian-Xiao; Hu, Yun-Xia; Xu, Xin-Hua; Cheng, Li-Hua
Highlights: The bEPS with higher interfacial energy showed the highest fouling rate. The sEPS of S. obliquus was dominated by proteins but C. vulgaris was carbohydrates. The fouling of S. obliquus was mainly caused by sEPS whereas that of C. vulgaris was cells. The fouling behaviors in two stages were found different due to structural evolution. Abstract: Membrane fouling was still a challenge for the potential application of forward osmosis (FO) in algae dewatering. In this study, the fouling behaviors of Chlorella vulgaris and Scenedesmus obliquus were compared in the FO membrane filtration process, and the roles of their soluble-extracellular polymeric substances (sEPS) and bound-EPS (bEPS) in fouling performance were investigated. The results showed that fouling behaviors could be divided into two stages including a quickly dropped and later a stable process. The bEPS of both species presented the highest flux decline (about 40.0%) by comparison with their sEPS, cells and broth. This performance was consistent with the largest dissolved organic carbon losses in feed solutions, and the highest interfacial free energy analyzed by the extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) theory. The chemical characterizations of algal foulants further showed that the severe fouling performance was also consistent with a proper ratio of carbohydrates and proteins contents in the cake layer, as well as the higher low molecular weight (LMW) components. Compared with the bEPS, the sEPS was crucial for the membrane fouling of S. obliquus, and an evolution of the membrane fouling structure was found in both species at the later filtration stage. This work clearly revealed the fundamental mechanism of FO membrane fouling caused by real microalgal suspension, and it will improve our understanding of the evolutionary fouling performances of algal EPS. Graphical abstract: Image, graphical abstract